Answer: g(x)-f(x)=8x-16
Explanation:
f(x)=-3x+4 (I am assuming "-3+4" is a typo and it is "-3x+4")
g(x)=5x-12
g(x)-f(x)=(5x-12)-(-3x+4)=5x+3x-12-4=8x-16
Just remember BODMAS, which B= brackets O= Order D= Division M= Multiply A=Addition and S=Subtract
So first you solve the brackets so 44+22 is 66
So 66-4+12 so 66-4 is 62
62+12 is 74
So now you have got 74 divided by 2 which is 37
Hope this helps xx
Answer:
Step-by-step explanation:
fe . seFgrgaerugaieurhrgHRGIQEHRIUGA EIUG IAUERG
Divide 6 by -8 to get the variable alone!
6/-8 < division< equation
Answer:
the correct answer is NO. hardy should have multiplied by the scale factor to find the missing length.
Step-by-step explanation:
dont got one hehehe